VD_FINDINFO Jug / 2016 / 271 vom 10. März 2016 - VD Tribunal cantonal (2016)
ACTE D'ACCUSATION, DROIT D'ÊTRE ENTENDU, PRINCIPE DE L'ACCUSATION | 29 al. 2 Cst., 356 CPP (CH), 398 al. 4 CPP (CH), 9 CPP (CH)